2023
DOI: 10.3390/toxins15020107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Adsorption Efficacy of Bentonite on Aflatoxin M1 Levels in Contaminated Milk

Abstract: The existence of aflatoxin M1 (AFM1) in raw milk results in economic losses and public health risks. This research aims to examine the capability of bentonite to adsorb and/or eliminate AFM1 from various raw milk types. In addition, the effects of numerous bentonites (HAFR 1, 2, 3 and 4) on the nutritional characteristics of the milk were studied. Our findings revealed that goat milk had the highest value of AFM1 (490.30 ng/L) in comparison to other milks. AFM1 adsorption was influenced by applying bentonite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
1
0
3
Order By: Relevance
“…In a previous Sudanese investigation, Ali et al [ 26 ] also revealed AFM1 in all raw milk samples tested with concentrations ranging from 0.1 to 2.52 µg/L. In 2023, Hamed et al [ 27 ] used HPLC-FD to analyze raw cow milk from Egypt, and detected AFM1 in 88% of samples with a maximum concentration of 0.122.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous Sudanese investigation, Ali et al [ 26 ] also revealed AFM1 in all raw milk samples tested with concentrations ranging from 0.1 to 2.52 µg/L. In 2023, Hamed et al [ 27 ] used HPLC-FD to analyze raw cow milk from Egypt, and detected AFM1 in 88% of samples with a maximum concentration of 0.122.…”
Section: Discussionmentioning
confidence: 96%
“…В ходе этой трансформации AFB1 вызывает образование реактивных перекисей. Компоненты молока коров, особенно жир, обезжиренные сухие вещества и белки, подвергаются воздействию присутствия AFM1, и их уровень снижается [3]. Это было связано с нарушением иммунного ответа у молочных коров из-за негативного влияния AFM1 [4,5].…”
Section: введение / Introductionunclassified
“…Yang et al, 2020). Medidas de manejo adequadas e estratégias de prevenção, como o uso de aditivos antimicotoxinas, podem ser necessárias para garantir a segurança e o desempenho adequado dos animais (Assaf et al, 2019;Gallo et al, 2020;Hamad et al, 2023;Luo et al, 2020;Rosim et al, 2018;Vila-Donat et al, 2019).…”
Section: Micotoxinas No Leiteunclassified
“…A busca por soluções viáveis levou à exploração de aditivos alimentares antimicotoxinas como uma abordagem promissora para reduzir os riscos da exposição das vacas em lactação às micotoxinas. Os aditivos antimicotoxinas, capazes de se ligar às micotoxinas e reduzir sua biodisponibilidade (Almeida Rego et al, 2021;Hamad et al, 2023), oferecem a possibilidade de minimizar os impactos negativos das micotoxinas na saúde e no desempenho dos bovinos.…”
Section: Introductionunclassified